Variable metaplastic entities in pleomorphic adenoma - a review of a rare case report with a note on its significance - Mahapatra, Niva; Bhuyan, Lipsa; Dash, Kailash Chandra; Mishra, Pallavi (Archive of Oncology, 2023)
Pleomorphic adenoma is the most common benign salivary gland neoplasm principally affecting the parotid gland of the salivary gland and the palate of the minor salivary gland. The term pleomorphic is assigned due to its varied histopathological presentation. We hereby describe a rare case of pleomorphic adenoma in a male patient in his 7th decade of life complaining of swelling in the hard palate for the past 3 years. This case report emphasizes the unique representation of squamous and lipomatous differentiation which was erroneously diagnosed as OSCC or mucoepidermoid carcinoma. We have also included a literature search of such cases that exhibited lipomatous and squamous differentiation in PA listed from the last 10 years.Key words: Pleomorphic adenoma, minor salivary gland, lipomatous differentiation, squamous differentiation.
Keywords: Pleomorphic adenoma, minor salivary gland, lipomatous differentiation, squamous metaplasia